Coping with Academic Stress among Muslim Adolescents: The Mediating Role of Tawakkal and Parental Religious Socialization - Melani Nur Cahya (Islamic Counseling and Parenting Journal, 2025)
This research examines how Muslim adolescents cope with academic stress through the mediating role of Tawakkal (effortful trust in Allah) and parental religious socialization. Using a qualitative multiple case-research design, data were collected from 15 Muslim adolescents, 10 parents, and 5 school informants in Indonesia through semi-structured interviews, observations, and documents. The results show that adolescents experience academic stress as an educational and moral–spiritual burden arising from heavy workloads, high-stakes examinations, dual religious–general curricula, and strong parental aspirations. Tawakkal functions as a key coping resource: when understood as “maximum effort followed by trust in Allah,” it supports cognitive reappraisal, emotional regulation, and more hopeful interpretations of success and failure. Cross-case analysis reveals three coping profiles anchored, ambivalent, and fragile Tawakkal shaped by the quality of parental religious socialization, particularly the balance between supportive and controlling religious messages. The research concludes that Tawakkal is a psychologically meaningful construct that mediates between family-based religious guidance and adolescents.